Implementation of National Education Standards (Case Study at SDN Sukadana Ciparay Bandung Regency) - Muchtarom Muchtarom; Ai Matin Shopwan Sumarni; Marpuah Marpuah; Muhamad Matin Shpowan Amarullah (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the importance of implementing national education standards to improve the quality of education. This study aims to describe the implementation of educational standards at SDN Sukadana Ciparay, Bandung Regency. This study uses a qualitative research method with a case study approach and is descriptive in nature. The place and time of this research is SDN Sukadana Ciparay, Bandung Regency in the Odd Semester 2023/2024. Data collection techniques namely observation, interviews and documentation. The informants/sources of information in this study were the Principal of SDN Sukadana Ciparay, Bandung Regency, the Wakasek of SDN Sukadana Ciparay, Bandung Regency, and the teachers of SDN Sukadana Ciparay, Bandung Regency. Data analysis techniques carried out were data reduction, data presentation, and verification. The results of this study explain that: 1) The implementation of national education standards at SDN Sukadana Ciparay Bandung Regency has not been able to meet the eight national education standards, 2) Aspects that need to be improved from content and process standards are guidance and counseling services, curriculum structure and curriculum development, implementation of learning, quality of class management, learning resources, quality of lesson plans, planning the learning process, and 3) Standard content of Ciparay Elementary School, Bandung Regency has challenges, namely the Curriculum of SD Sukadana such as counselors and resource persons. Curriculum orientation must also support the subjects tested.